Sosialisasi Edukasi Menabung Sejak Dini di SDN 124404 Kelurahan Simarito Kota Pematangsiantar - Darwin Damanik; Pawer Darasa Panjaitan; Fariaman Purba; Pandapotan Damanik; Manres Nababan; Savirgi B Amri; Jun Kifran Manik (Jurnal Nusantara Berbakti, 2024)
The high purchasing power of society and within lengthy periods will cause the state falls into inflation. Inflation has its influence on domestic savings. Hence, the government tries to limit the amount of money which circulates and reduces inflation risk by offering higher interest rates for the people who deposit their money in national banks. The socialization program of early saving is carried out with the purpose of creating national program in creating a generation who isable to manage their finances well. Other than that, the program hopefully has the ability to leverage the interest in saving for children. The children may develop the habit into an insurance for their later life, and autonomously learn to save and to be responsible in managing the money,hence the goals of the program.Teaching the children to save early may also develop positive personality; to save means teaching the children how to be patient, and saving is useful for future savings.